Sustaining the Muslim institution of marriage in Malaysia : an analytical study of qur'anic stories - Nor Zatu Amni binti Mohammad (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
There are 10 major problems that endanger the Muslim institution of marriage in Malaysia. They are: (1) irresponsibility; (2) weak Islamic background; (3) third party interference; (4) cultural differences; (5) sexual issues; (6) financial crisis; (7) career dilemma; (8) health problems; (9) moral decay; and (10) communication obstacles. In order to overcome these problems and sustain the Muslim institution of marriage, there is a need to assess such problems through Qur'anic stories of husbands and wives, and deriving important lessons to form concrete modules of JAKIM's post-marriage courses. This qualitative study primarily uses historical methodology through library research. Descriptive approach was utilised to portray the stories of husbands and wives in the Qur'an. Subsequently, analytical approach was applied to assess the major problems in marriage before providing relevant suggestions for JAKIM's post-marriage modules. The three key results of this research are: (1) JAKIM's post-marriage courses are the best platforms to propagate the Qur'anic stories of husbands and wives to married couples in Malaysia, and therefore it is very important not to mix these stories with unknown sources or details; (2) Qur'anic stories of husbands and wives prove that marital life is an arena for jihad, which means, married couples need to strive and put their utmost efforts to strengthen their marital relationship; and (3) virtues, such as humility, patience, and honesty are the vanguards for marriage while vices, such as arrogance, greed, and infidelity are the destroyers of marriage.